UNDERSTANDING FACULTY PERCEPTIONS OF THE CURRENT STATE OF HIGHER EDUCATION GOVERNANCE IN KAZAKHSTAN - Sarinzhipov, Asian; Sagintayeva, A.; Kurakbayev, Kairat (My University, 2012)
"In this paper, we have examined faculty perceptions of the current state of higher education governance in Kazakhstan. The purpose was to analyse the faculty's opinions and attitudes towards governance in their institutions. Several conclusions can be drawn from the findings. The first is that faculty was mostly unsatisfied with their level of involvement in governance, particularly in terms of the ways in which they communicate with upper management. Faculty would like to see proper feedback mechanisms in their communication channels with Vice Rectors and Rectors. Interestingly, the majority of faculty respondents claim that contemporary governance systems cannot respond appropriately to new social and academic realities. Most faculty members take their inactiveness for granted as they do not feel that their decisions will have an impact on institutional governance. However, the research has shown that faculty members are involved at the departmental level and feel comfortable about that." - ...